Penerapan Pewarnaan Titik pada Graf dalam Penyusunan Lokasi Duduk Menggunakan Algoritma Greedy Berbantuan Microsoft Visual Basic 6.0 - Halimah Turosdiah; Armiati Armiati; Meira Parma Dewi (UNIVERSITAS NEGERI PADANG, 2014)
Abstract – Graph colouring has been applied in various problems. Graph colouring in particular vertex colouring is also applicable for arranging seat location. The arranging of seat location in many events is very concerned. Because it can avoiod rottenness that possibly happen. Vertex colouring for arranging seat location is started with representating participant’s seat as vertex and participant’s seat that adjacent with right or left or front or behind it is connected by edge, so that participant’s seat which adjacent is not placed by participant’s from the same school. Greedy algorithm will be used in this arranging of seat location that applied later in Microsoft Visual Basic 6.0 software. From the testing of program obtained that the program of arranging seat location has made exact solution where participant’s from the same school is not adjacent sit. Keywords – Vertex colouring, Arranging seat location, Greedy algorithm